Chemical by-Product Diagnostic Technique for Gas Insulated Switchgear Condition Monitoring - Visa Musa Ibrahim; Zulkurnain Abdul-Malek; Nor Asiah Muhamad (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
Chemical by product diagnostic technique is an efficient, cost-effective and reliable diagnostic technique for gas insulate switchgear condition monitoring in view of its high sensitivity and anti- internal and external electromagnetic interference and noise. In this research paper, coaxial simulated gas insulated switchgear chamber and four different types of artificial defect were designed to cause partial discharge that will simulate the decomposition of sulphur hexafluoride gas in the chamber when energize. Fourier transform infrared spectrometer was used as the method of chemical by-product technique to detect the SF6 decomposition product and its concentration. Different numerous by-products were detected (SO2, SOF2, SO2F2, SO2F10, SiF4, CO, C3F8, C2F6 ) under this experiment using four different types of defect and the by-products differs with the type of defect and the generation rate. Gas insulated switchgear health condition can be feasibly diagnosed by analyzing the decomposition products of SF6 to identify its fault.